2019
DOI: 10.31563/1684-7628-2019-51-3-10-13
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Application of Solid Products of Biogas Installation on Oil-Polluted Soils

Abstract: The article contains the results of scientific research on the use of solid products from the processing of poultry manure in a biogas plant of OOO NPO Agrobiogaz, St. Petersburg (hereinafter referred to as TBU or solid bio-fertilizer) on soils contaminated with oil products. Solid biogas plant processing products are a non-traditional type of organic fertilizer. The chemical composition of biofertilizer was determined: 1 ton of a natural substance contains on average 16,5 kg/ton of total nitrogen, 20 kg/ton o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Laboratory analysis of the content of heavy metals in soil and potato tubers showed approximately the same low content in all variants. It is also confirmed by studies carried out under the land monitoring program, confirming the ecological purity of the territory of the Chuvash Republic [7,8].…”
Section: Research Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…Laboratory analysis of the content of heavy metals in soil and potato tubers showed approximately the same low content in all variants. It is also confirmed by studies carried out under the land monitoring program, confirming the ecological purity of the territory of the Chuvash Republic [7,8].…”
Section: Research Resultssupporting
confidence: 54%
“…Numerous results of scientific research on the cultivation of agricultural crops using only organic fertilizers (semi-rotted manure, compost, peat), urban wastewater sludge, as well as by-products of the food industry and waste processing (liquid and solid products of a biogas plant, horn-hoofed shavings, bone meal, cake, etc.) showed their high economic efficiency [1], [2], [3], [4], [5], [6], [8], [9], [12], [ 19], [20], [21]. The research carried out in greenhouses showed that by-products of industrial production, i.e., products of a biogas plant, municipal wastewater sludge, etc.…”
Section: Introductionmentioning
confidence: 99%